2023
DOI: 10.3390/d15040486
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Effects of Multi-Scale Landscape Pattern and Habitats Attributes on Taxonomic and Functional Diversity of Urban River Birds

Abstract: Several studies have revealed that urban rivers with relatively complete habitat structures can support a high level of biodiversity in urban areas. However, few studies have analyzed the impact of the plan, design, and management of multi-scale urban riverside green space on bird communities by assessing several aspects of diversity (e.g., taxonomic and functional). In this study, we explored bird community variation (taxonomic and functional) among three rivers (28 sampling sites) with different levels of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 78 publications
2
5
0
Order By: Relevance
“…Furthermore, our moderate functional evenness indices indicate a balanced utilisation of resources and thus productivity (Mason et al, 2005). Our results are consistent with reports that diversity in environmental conditions, especially in vegetation types, can increase the diversity of bird communities (BirdLife South Africa, 2022; Mao et al, 2023), and a similar observation was reported in central Argentina (Leveau, 2019; Tilman et al, 1997).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Furthermore, our moderate functional evenness indices indicate a balanced utilisation of resources and thus productivity (Mason et al, 2005). Our results are consistent with reports that diversity in environmental conditions, especially in vegetation types, can increase the diversity of bird communities (BirdLife South Africa, 2022; Mao et al, 2023), and a similar observation was reported in central Argentina (Leveau, 2019; Tilman et al, 1997).…”
Section: Discussionsupporting
confidence: 93%
“…Forest habitats tend to provide more resources than other vegetation types in the Eastern Cape province in South Africa (Bitani et al, 2020;Leaver & Cherry, 2020;Maseko et al, 2020;Oatley, 1989). Similarly, our finding of a relatively large number of different forest bird species may be attributed to those abundant resources although there are no predictable fruit patterns in forest patches (Gumede et al, 2022;Hart et al, 2013) of which may influence bird movement between the forest patches, and thus, associated dispersal services (Gumede et al, 2022;Mao et al, 2023;Maseko et al, 2020). Furthermore, the protected biodiversity conservation areas experience minimal anthropogenic habitat disturbance and thus adequate structural resources, thereby providing a safe living place for certain bird species (Evans et al, 2006;Gomes et al, 2008;Gregory et al, 2003;Lecina-Diaz et al, 2019;Maseko et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations